Serosurvey of Rickettsia spp. in dogs and humans from an endemic area for Brazilian spotted fever in the State of São Paulo, Brazil Sorologia para Rickettsia spp. em cães e humanos de uma área endêmica para febre maculosa brasileira no Estado de São Paulo, Brasil - Adriano Pinter; Maurício C. Horta; Richard C. Pacheco; Jonas Moraes-Filho; Marcelo B. Labruna (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
The present study provides a rickettsial serosurvey in 25 dogs and 35 humans in an endemic area for Brazilian spotted fever in the State of São Paulo, where the tick Amblyomma aureolatum is the main vector. Testing canine and human sera by indirect immunofluorescence against four Rickettsia antigens (R. rickettsii, R. parkeri, R. felis and R. bellii) showed that 16 (64%) of canine sera and 1 (2.8%) of human sera reacted to at least one of these rickettsial antigens with titers ³ 64. Seven canine sera and the single reactive human serum showed titers to R. rickettsii at least four times those of any of the other three antigens. The antibody titers in these 7 animals and 1 human were attributed to stimulation by R. rickettsii infection. No positive canine or human serum was attributed to stimulation by R. parkeri, R. felis, or R. bellii. Our serological results showed that dogs are important sentinels for the presence of R. rickettsii in areas where the tick A. aureolatum is the main vector of Brazilian spotted fever. Este estudo avaliou a ocorrência de anticorpos anti-Rickettsia em 25 cães e 35 humanos, em uma área endêmica para a febre maculosa brasileira no Estado de São Paulo, onde o principal vetor é o carrapato Amblyomma aureolatum. Soros dos cães e humanos foram testados pela técnica de imunofluorescência indireta contra quatro antígenos de riquétsias (R. rickettsii, R. parkeri, R. felis, R. bellii), mostrando que soros de 16 (64%) cães e 1 (2,8%) humano reagiram com títulos ³ 64 para pelo menos um dos antígenos de riquétsias. Sete soros caninos e o único soro humano reativo demonstraram títulos para R. rickettsii no mínimo quatro vezes maior do que aqueles para os outros antígenos de riquétsias. Os títulos de anticorpos nesses cães e um humano foram considerados homólogos a R. rickettsii, enquanto que nenhum soro de cão ou humano foi considerado reativamente homólogo para R. parkeri, R. felis ou R. bellii. Os resultados sorológicos mostraram que cães são importantes sentinelas para a presença da bactéria R. rickettsii em áreas onde o carrapato A. aureolatum é o principal vetor da febre maculosa brasileira.